The Jewish way in love and marriage - Lamm, Maurice (Harper & Row, 1980)
With the traditions and laws of the Bible as his base, Rabbi Lamm portrays the great effort Judaism has expended in creating and maintaining the institution of marriage. He shows how indispensable it is to society as a whole and to the Jewish community in particular. He summarizes the traditional views of marriage and explores the outward symbols, practices, and customs of the traditional wedding ceremony, explaining their significance. At the same time, he breaks clarifies and explores Jewish law to such topics as premarital sex, homosexuality, and mixed marriages.